2023
DOI: 10.1590/0103-8478cr20210554
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipid sources on the fatty acid profile of swine fat: a review

Abstract: Swine production has focused its efforts to reduce the amount and improve the quality of fat deposited on carcass. Due to the association of the lipid profile with cardiovascular diseases, researches have been developed to understand how the deposition occurs and to improve the fatty acid profile of swine fat. Among the factors that affect the fat composition, race, sex, and diet, the third one has the greatest impact. Lipid inclusion seems to be a promising way to modulate the lipid profile of fat in pig carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…3 -d). Monounsaturated fatty acids are cardioprotective, and α-linolenic acid, as an ω-3 fatty acid, can prevent cardiovascular disease by reducing LDL levels and the ratio of cholesterol and triglycerides to HDL ( Alencar & Kiefer, 2023 ). Aaslyng and Schäfer (2007) found that adding α-linolenic acid can make pork taste like fried fish or fish liver oil.…”
Section: Resultsmentioning
confidence: 99%
“…3 -d). Monounsaturated fatty acids are cardioprotective, and α-linolenic acid, as an ω-3 fatty acid, can prevent cardiovascular disease by reducing LDL levels and the ratio of cholesterol and triglycerides to HDL ( Alencar & Kiefer, 2023 ). Aaslyng and Schäfer (2007) found that adding α-linolenic acid can make pork taste like fried fish or fish liver oil.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, considering the product consumption perspective, higher levels of PUFA in pork can make pork more susceptible to oxidative rancidity and reduce shelf life [9], which may be disadvantageous for the daily storage of pork. In addition, as the most widely consumed meat, pork is usually made unbalanced in its n-6/n-3 PUFA ratio by conventional feeding methods [34], and the unbalanced n-6/n-3 PUFA ratios are considered to be one cause of cardiovascular disease [35]. Therefore, considering the health aspects, the excessive increase in C18:2n-6 percentage resulting from feeding large amounts of DDGS may reduce the nutritional value of pork.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%